2015
DOI: 10.1111/pedi.12255
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone concentration and insulin sensitivity in young men with type 1 and type 2 diabetes

Abstract: Objective Reduced testosterone, a recognized comorbidity of reduced insulin sensitivity (IS) and type 2 diabetes (T2D), has also been reported in adult males with type 1 diabetes (T1D). However, there are limited data on how early reduced testosterone occurs, and whether it is related to the reduced IS in T1D. Leptin, a modulator of the HPG-axis, may also influence testosterone in T1D. We hypothesized that IS and leptin would be associated with total testosterone (TT), and free androgen index (FAI) in adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Previous evidence demonstrated that low serum T concentrations and poor semen quality were associated with visceral obesity [7,16], IR, and type 2 diabetes [17,18]. Additionally, obesity can cause and aggravate IR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence demonstrated that low serum T concentrations and poor semen quality were associated with visceral obesity [7,16], IR, and type 2 diabetes [17,18]. Additionally, obesity can cause and aggravate IR.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that testosterone induces meal free fatty acid (FFA) uptake preferentially into abdominal subcutaneous adipose tissue (SAT) resulting in a decreased uptake in visceral adipose tissue (VAT) [24]. The biological effect of testosterone is most likely enhanced by decreasing leptin levels, and an inverse correlation between leptin levels and testosterone was reported by Kelsey et al [25]. Even though we did not measure testosterone levels, we assume that decreasing leptin levels contributed to a decrease of visceral fat and an increase of subcutaneous skinfold thickness in the trunk area induced by testosterone.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, men with T1DM do not appear to have a high prevalence of androgen deficiency (45,52). However, Maric et al demonstrated that diabetes without renal disease was associated with decreased testosterone and estrogen levels compared with healthy nondiabetic adult men.…”
Section: Effect Of Type 1 Diabetes On Androgen and Estrogen Levelsmentioning
confidence: 94%
“…Poor glycemic control in Korean men with T2DM resulted in increased levels of fasting plasma glucose and HbA 1c values, the major markers of diabetes, which appeared to be associated with testosterone deficiency (53). In addition, diabetic men had also lower levels of sex hormonebinding globulin (SHBG) compared with nondiabetic men (10,52). In fact, several prospective studies have shown that diabetes and metabolic syndrome are more strongly predicted by low SHBG than by low testosterone (41,55,128).…”
Section: Effect Of Type 2 Diabetes On Androgen and Estrogen Levelsmentioning
confidence: 96%